Pengembangan Alat Pelontar Shuttlecock sebagai Alat Latihan Netting - Pamungkas Nur Hidayat; Bimo Alexander; Andri Arif Kustiawan; Agus Pribadi (MAN Insan Cendekia Jambi, 2026)
This study aims to develop an economical shuttlecock launcher for badminton netting practice. The method used is Research and Development (R&D) with the ADDIE model. Subjects included one expert , 10 students (small-group trial), and 20 athletes from PB Diamond (large-group trial). Data were collected via Likert-scale questionnaires and analyzed using descriptive percentages. The results showed that the device, made of hollow iron and a 12-Volt DC motor, was assembled for Rp1,750,000. In the small-group trial, it scored 416 (83.2%), categorized as